Nourishing Life Foodways and Humanity in an African Town. - Huhn, Arianna (Food, Nutrition, and Culture Ser., 2020)
In this accessible ethnography of a small town in northern Mozambique, everyday cultural knowledge and behaviors about food, cooking, and eating reveal the deeply human pursuit of a nourishing life. This emerges less through the consumption of specific nutrients than it does in the affective experience of alimentation in contexts that support vitality, compassion, and generative relations. Embedded within central themes in the study of Africa south of the Sahara, the volume combines insights from philosophy and food studies to find textured layers of meaning in a seemingly simple cuisine.